A finite rotation shell theory with application to composite structures - Gruttmann, Friedrich; Klinkl, Sven; Wagner, Werner (European Journal of Computational Mechanics, 1995)
In this paper we derive a finite element formulation for geometrical nonlinear shell structures. The formulation bases on a direct introduction of the isoparametric finite element formulation into the shell equations. The element allows the occurence of finite rotations which are described by a rotation tensor. A layerwise linear elastic material model for composites is chosen. The consistent linearization of all equations leads to quadratic convergence behaviour within the nonlinear solution procedure. Examples show the applicability and effectivity of the developed element.